'He's still with these girls': exploring perceptions of HIV risk among men with behaviourally bisexual male partners. Issue 12 (1st December 2016) - Williams, Whitney; Goldenberg, Tamar; Andes, Karen L.; Finneran, Catherine; Stephenson, Rob
Abstract: Recent studies have called for more nuanced research into the relationships between behaviourally bisexual men and their sexual partners. To address this, we conducted a longitudinal qualitative study with self-identifying gay men; participants took part in timeline-based interviews and relationship diaries. We conducted a thematic analysis of verbatim transcripts to understand how relationship motivations, emotions and relationship dynamics influenced perceptions of HIV risk with behaviourally bisexual male partners. Participants described how partnership types (main and casual) and relationship dimensions (exclusivity, commitment, emotional attachment and relationship designation) strongly influenced perceptions of HIV risk and shaped their decisions to choose behaviourally bisexual male sex partners. Results reveal the crucial role relationship dynamics play in the shaping of HIV risk perceptions, sexual decision-making and HIV risk between partners, and provide potential insight on how to message HIV risk to gay men and their behaviourally bisexual male partners. It is imperative that HIV prevention is able to message key concepts of risk, decision-making and partner negotiation in a way that does not act to stereotype or create stigma against behaviourally bisexual men and their male partners.